Isolation and Phenotypic Characterization of Virulent Bacteriophages Against Multidrug-Resistant Escherichia coli and Its Phage-Resistant Variant from Sewage Sources - Fikadu A; Amankwah S; Alemu B; Alemu Y; Naga A; Tekle E; Kassa T (Infection and Drug Resistance, 2024)
Ashetu Fikadu,1,2 Stephen Amankwah,3 Bikila Alemu,1,4 Yared Alemu,1 Adisu Naga,5 Esayas Tekle,6 Tesfaye Kassa1 1School of Medical Laboratory Sciences, Jimma University, Jimma, Ethiopia; 2Department of Medical Laboratory Sciences, Dambi Dollo University, Dambi Dollo, Ethiopia; 3Department of Medical Laboratory, Accra Medical Centre, Accra, Ghana; 4Medical Microbiology Laboratory Unit, Jimma Medical Center, Jimma, Ethiopia; 5Department of Public Health Emergency Management, Kelem Wollega Zone Health Office, Dambi Dollo, Ethiopia; 6Department of Medical Laboratory, Wollega University, Nekemte, EthiopiaCorrespondence: Tesfaye Kassa, School of Medical Laboratory Sciences, Jimma University, P. O. Box 788, Jimma, Ethiopia, Tel +251931057195, Email ktes36@gmail.com; tesfaye.kassa@ju.edu.etPurpose: The use of lytic bacteriophages for the control or elimination of pathogenic multidrug-resistant (MDR) bacteria is the promising alternative. However, the emergence of resistant bacterial variants after phage application may challenge its therapeutic benefit. In this study, we aimed to isolate candidate phages from sewage samples against two MDR Escherichia coli as well as their phage-resistant variant.Methods: MDR E. coli isolates (n = 10) obtained from Jimma Medical Center that had been properly identified and stored were used to isolate bacteriophages. Two lytic coliphages were isolated from hospital sewage samples following standard protocols. Upon single phage infection, phage-resistant variant quickly evolved serving as a new host for the isolation of a third lytic phage. This virulent phage’s lytic activity against both its host and the wild host was investigated. The host infectivity of the various cocktails was assessed, and each phage’s biological properties were studied.Results: Out of the first round of phage isolation process, two lytic phages were identified as VBO-E. coli 4307 and VBW-E. coli 4194. When exposed to VBO-E. coli 4307, the wild-type E. coli 4307 developed resistant variants. A third phage (VBA-E. coli 4307R) was isolated specific to this resistant variant (E. coli 4307R) under optimum condition. For VBO-E. coli 4307, VBW-E. coli 4194, and VBA-E. coli 4307R, the plaque assays generated under comparable conditions were 2.13 × 1010 PFU mL− 1, 9.17 × 1012 PFU mL− 1, and 3.3 × 1010 PFU mL− 1, respectively. These phages have nearly identical stability and lytic ability but differ greatly in their host ranges for VBA-E. coli 4307R.Conclusion: While the wild-type MDR pathogen could easily evolve resistance when exposed to a single phage infection by VBO-E. coli 4307, it is still possible to isolate a novel bacteriophage from environmental samples that is effective against the phage-resistant variants. This indicates that it is possible to manage the effects of phage resistance pathogens even if they are MDR.Keywords: phage, phage-resistance, E. coli, multidrug resistance, sewage, Jimma Medical Center